Visual Basic 2012 unleashed - Del Sole, Alessandro (Sams, 2013)
Fully updated for Windows 8 support, .NET 4.5, and Windows Phone development, this is the most comprehensive, practical reference to modern programming with Visual Basic 2012. Written by Visual Basic MVP Alessandro Del Sole, a long-time leader of the global VB community, this book illuminates the core to the VB language and demonstrates its effective use in many current programming scenarios. Del Sole covers both Visual Basic 2012 Professional Edition for professional developers and the Express Edition for hobbyists, novices, and students. Writing for VB programmers at all levels of experience, he walks through using VB 2012 for data access, Windows desktop. Windows Phone user interface development, networking, communication, and much more. For those moving form structured languages--including VB 6--Del Sole offers detailed guidance on building effective object-oriented code. He also demonstrates how to make the most of Microsoft's updated .NET 4.5 platform to write more robust and powerful software.--